Distinction between Antimicrobial Resistance and Putative Virulence Genes Characterization in Plesiomonas shigelloides Isolated from Different Sources - Samy Selim; Mohammed S. Almuhayawi; Shadi Ahmed Zakai; Ahmed Attia Salama; Mona Warrad (Antibiotics, 2022)
Plesiomonas shigelloides are gram-negative, thermotolerant, motile, and pleomorphic microorganisms that are only distantly related to those of the Enterobacteriaceae and Vibrionaceae families. One of the most common sources of P. shigelloides contamination is human stool, but it may also be found in a wide range of other animals, plants, and aquatic habitats. Antimicrobial resistance in P. shigelloides from seawater and shellfish was investigated, and pathogenicity involved genes were characterized as part of this study. Out of 384 samples of shellfish, 5.7% included P. shigelloides. The presence of P. shigelloides was also discovered in 5% of the seawater sampled. The antimicrobial resistance of 23 P. shigelloides isolates derived from those samples was investigated. All isolates were sensitive to nalidixic acid, carbenicillin, cephalothin, erythromycin, kanamycin, tetracycline, and ciprofloxacin in the study. Several strains isolated from diseased shellfish were tested for virulence in shellfish by intraperitoneal injections. The LD50 values ranged from 12 × 108 to 3 × 1012 cfu/shellfish. When looking for possible virulence factors that may play a significant role in bacterial infection in the current study, we found that all of these genes were present in these strains. These include genes such as elastase, lipase, flagellin, enterotoxin, and DNases. According to these findings, shellfish may serve as a reservoir for multi-resistant P. shigelloides and help spread virulence genes across the environment.